2016
DOI: 10.1111/aogs.13024
|View full text |Cite
|
Sign up to set email alerts
|

Medical and social egg freezing: internet‐based survey of knowledge and attitudes among women in Denmark and the UK

Abstract: This study indicates that there is widespread awareness and support of the availability of eggs freezing for reproductive planning. Reassurance regarding its efficacy appears more important than its potential adverse effects on their health or that of future children, or the costs of the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 17 publications
(22 reference statements)
3
51
1
Order By: Relevance
“…Oocyte cryopreservation on medical grounds is indisputably an advantageous linear solution and well-accepted socially [ 80 ]. From a medical, psychological and bioethical stand point, oocyte freezing for nonmedical reasons raises controversy within the scientific community due to the multifaceted underlying reasons evoking it.…”
Section: Discussionmentioning
confidence: 99%
“…Oocyte cryopreservation on medical grounds is indisputably an advantageous linear solution and well-accepted socially [ 80 ]. From a medical, psychological and bioethical stand point, oocyte freezing for nonmedical reasons raises controversy within the scientific community due to the multifaceted underlying reasons evoking it.…”
Section: Discussionmentioning
confidence: 99%
“…Even in populations that have a good understanding of age‐related infertility, women continue to defer childbearing . In a survey of over 1000 women in the UK and Denmark, 89% considered reproductive planning to be an acceptable indication for SEF . These positive attitudes towards SEF are reflected by an almost threefold increase in the number of eggs frozen in the UK, from 2476 in 2008 to 7047 in 2013 .…”
Section: Social Factorsmentioning
confidence: 99%
“…Social, personal, educational and financial pressures often lead women to delay starting a family until the late thirties, by which time the chance of getting pregnant is compromised by low fecundity rates and an increased risk of miscarriage if they become pregnant. In an internet-based survey on knowledge and attitudes of women towards social egg freezing in UK and Denmark, it was found that 83% women were aware about egg freezing option and 89% considered it acceptable for social reasons [70]. Characteristics significantly limited to the intention of egg freezing included being single, age under 35 years, childlessness and a history of infertility.…”
Section: Social Egg Freezing- Race Against Time or Smoke And Mirrors?mentioning
confidence: 99%
“…Age and oocyte yield have a substantial effect on the pregnancy prospects in such patients [70]. The existing studies and research do not offer any clear – cut guidelines for clinical handling.…”
Section: The Problem Of Poor Ovarian Responsementioning
confidence: 99%